IMPLEMENTATION OF IT SERVICE MANAGEMENT (ITSM) IN SERVICE LEVEL MANAGEMENT AND CAPACITY AND PERFORMANCE MANAGEMENT PROCESSES - Ardia Cahyani Rahmasari; Ari Fajar Santoso; Dhata Praditya (Publikasi Indonesia, 2025)
IT Service Management (ITSM) is essential for organizations to address IT challenges and deliver services that meet user needs, improve quality, and reduce costs. For government agencies like Diskominfo Kota Bandung, ITSM offers a structured approach to optimizing IT in service delivery. While Diskominfo follows the Electronic-Based Government Letter (SPBE) guidelines aligned with ISO 20000, it has yet to implement ITIL standards. The organization faces challenges in managing service levels, including the absence of precise Service Level Requirements (SLR) and Service Level Agreements (SLA), and struggles with managing service capacity and performance. These challenges highlight the need for improvements in their ITSM processes. This study evaluates and enhances the ITSM processes at Diskominfo Kota Bandung, focusing on Service Level Management and Capacity and Performance Management, using the ITIL V3 framework as a best practice model. The research adopts a Design Science Research (DSR) methodology to create innovative, actionable solutions. Data was collected through interviews and assessments and analyzed using Capability Maturity Model Integration (CMMI) to identify improvement areas based on ITIL V3. The results show that the Service Level Management process is at Level 1 (Initial), while Capacity and Performance Management is partially at Level 2 (Repeatable). Recommendations are provided for improvements across people, processes, and technology to optimize ITSM practices and achieve higher maturity levels aligned with ITIL V3.